Characterizing the Ordinary Broad-line Type Ic SN 2023pel from the Energetic GRB 230812B - Srinivasaragavan, Gokul (2024)
We report observations of the optical counterpart of the long gamma-ray burst (GRB) GRB 230812B and its associated supernova (SN) SN 2023pel. The proximity (z = 0.36) and high energy (Eγ,iso ∼ 1053 erg) make it an important event to study as a probe of the connection between massive star core collapse and relativistic jet formation. With a phenomenological power-law model for the optical afterglow, we find a late-time flattening consistent with the presence of an associated SN. SN 2023pel has an absolute peak r-band magnitude of Mr = −19.46 ± 0.18 mag (about as bright as SN 1998bw) and evolves on quicker timescales. Using a radioactive heating model, we derive a nickel mass powering the SN of MNi = 0.38 ± 0.01 M⊙ and a peak bolometric luminosity of Lbol ∼ 1.3 × 1043 erg s−1. We confirm SN 2023pel’s classification as a broad-line Type Ic SN with a spectrum taken 15.5 days after its peak in the r band and derive a photospheric expansion velocity of vph = 11,300 ± 1600 km s−1 at that phase. Extrapolating this velocity to the time of maximum light, we derive the ejecta mass Mej = 1.0 ± 0.6 M⊙ and kinetic energy EKE = 1.3^+3.3-1.2 x 10^51 erg . We find that GRB 230812B/SN 2023pel has SN properties that are mostly consistent with the overall GRB-SN population. The lack of correlations found in the GRB-SN population between SN brightness and Eγ,iso for their associated GRBs across a broad range of 7 orders of magnitude provides further evidence that the central engine powering the relativistic ejecta is not coupled to the SN powering mechanism in GRB-SN systems.